2008
DOI: 10.1007/s11255-008-9353-8
|View full text |Cite
|
Sign up to set email alerts
|

Observations regarding the use of the aquaretic agent conivaptan for treatment of hyponatremia

Abstract: The treatment of hyponatremia, especially euvolemic and hypervolemic hyponatremia, has changed with the development of drugs which function as vasopressin receptor antagonists. These agents increase solute-free water excretion by the kidney resulting in an aquaresis. Conivaptan, a vasopressin receptor antagonist, has recently been approved by the FDA in the United States for use in the therapy of both euvolemic and hypervolemic hyponatremia. This report summarizes one center's experience with ten patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
3
6
1
Order By: Relevance
“…Our findings resembled those of other studies,[13142122] where there were no reports of neurological damage despite rapid correction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings resembled those of other studies,[13142122] where there were no reports of neurological damage despite rapid correction.…”
Section: Discussionsupporting
confidence: 91%
“…The magnitude of increase in serum sodium levels is a bit higher in our study compared to previous studies[72122] though the rate of correction is still within the recommended treatment guidelines for hyponatremia. [2] The faster correction of sodium in our study could be possibly due to the presence of a more elderly population and low baseline serum sodium levels.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The occurrence of hyponatremia with an SSRI is generally thought to result from the development of a SIADH-like syndrome and has been demonstrated to be improved following the use of vasopressin blocking drugs [21]. Vasopressin blocking drugs have been associated with water diuresis in a variety of clinical syndromes such as SIADH and congestive heart failure [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated changes in mentation and mobility in hyponatremic patients [17] and changes in bone structure and susceptibility to fracture have also been reported [18,19]. Interest in hyponatremia has been further stimulated by the recent development of specific vasopressin receptor blocking agents which can facilitate an increase in serum sodium levels in patients with clinically significant low levels [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%